Percepciones de los psicólogos sobre las funciones y alcances en los departamentos de consejería estudiantil. - Lara-Lomas, Lenin; Agualongo Amangandi, Joffre David; Bastidas Mora, Melanie Alejandra; Pinza Balarezo, Madellyn Pamela (Revista de Investigación en Salud VIVE)
Psychologists in educational settings promote students' emotional, social, and academic well-being, intervene in learning and behavioral difficulties, and foster inclusive environments for holistic development. Objective. To analyze educational psychologists' perceptions of their roles, work challenges, and the impact of current regulations on their performance within Student Counseling Departments. Methodology. The methodological approach was qualitative, non-experimental, and cross-sectional. Data were collected using the semi-structured interview technique, and the instrument was validated by specialists in the field. Results. The results indicate that, although the regulations have been updated by Ecuador's Ministry of Education, significant challenges remain, such as administrative workload, the number of students assigned per professional, discrepancies with professional profiles, lack of training in action protocols, and differences in resource access depending on institutional funding type. Conclusion. The work of psychologists in Student Counseling Departments emerges as an essential pillar for the socio-emotional well-being of the educational community, despite systemic challenges limiting their effectiveness.